Preliminary Phytochemical Analysis Of Some Important Indian Plant Species - VENKATA S. S. N. KANTAMREDDI,; Y. NAGENDRA LAKSHMI,; V. V. V. SATYANARAYANA KASAPU,; VENKATA S. S. N. KANTAMREDDI, (International Journal of Pharma and Bio Sciences, 2010)
This present study reports 84 methanolic extracts prepared from the 54 Indian plants belonging to 33 different families collected from the forest located in Eastern Ghats of India. A qualitative preliminary phytochemical screening was performed on aforesaid extracts for the presence of alkaloids, flavonoids, steroids and terpenoids. Each analysis was carried out in triplicate, which resulted a total of 22, 19, 37 and 30 plant species were found to give positive results for alkaloids (41%), flavonoids (35%), steroids (69%) and terpenoids (56%), respectively.